2018
DOI: 10.1111/1759-7714.12820
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of recovery parameters using patient‐controlled epidural analgesia for video‐assisted thoracoscopic surgery lobectomy in enhanced recovery after surgery: A prospective, randomized single center study

Abstract: BackgroundWe compared the effects of thoracic epidural analgesia (TEA) to conventional patient‐controlled analgesia (PCA) on several postoperative parameters of recovery after elective video‐assisted thoracoscopic (VATS) lobectomy.MethodsNinety‐eight patients undergoing elective VATS lobectomy were enrolled. The primary endpoint was pain score. Recovery of bowel function, length of stay in the postanesthesia care unit (PACU), duration of postoperative hospital stay, and complications were assessed. Continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
3
17
1
1
Order By: Relevance
“…These results were consistent with other studies. 26) However, there was no difference in the incidence of complications between the two groups at 48 hours after operation. Although the incidence of complications in TEA group was higher, the overall satisfaction of patients was higher in TEA group, which might be related to the better analgesic effect of TEA.…”
Section: Discussionmentioning
confidence: 83%
“…These results were consistent with other studies. 26) However, there was no difference in the incidence of complications between the two groups at 48 hours after operation. Although the incidence of complications in TEA group was higher, the overall satisfaction of patients was higher in TEA group, which might be related to the better analgesic effect of TEA.…”
Section: Discussionmentioning
confidence: 83%
“…El-Tahan [15] emphasized that t-PCEA usage could be associated with favorable postoperative pulmonary function, a low incidence of postoperative pulmonary complications, fast return of normal bowel function, and a shorter hospital stay after thoracic surgery. Zejun et al [14] also conducted a prospective randomized study, which showed that when compared with IVPCA, t-PCEA resulted in not only lower postoperative pain scores, but also earlier restoration of bowel function after VATS lobectomy. Tiippana et al [6] agreed that t-PCEA with local anesthetics and opioids was superior to IVPCA with opioids for post-thoracotomy pain and the recovery of pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…[2,19,23] Morphine has a good antinociceptive effect, but is associated with some well-known adverse effects, including respiratory depression, excessive sedation, nausea, vomiting, ileus, and constipation, [2,5,1921] all of which preclude its continuous use. Despite the use of different components in IVPCA, such as oxycodone or sufentanil rather than fentanyl, some studies [2,14] still showed that t-PCEA provided superior analgesia and less opioid-related complications compared to IVPCA in thoracic surgeries. In our hospital, fentanyl is routinely used in IVPCA for postoperative pain control in all kinds of surgeries, as it has a quicker onset and results in less sedation than morphine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced recovery after surgery (ERAS) programs have become increasingly popular in different fields of surgery over the past decade [ 11 ]. The concept of ERAS was originally put forward in the field of general surgery and colonic resection [ 12 ].…”
Section: Introductionmentioning
confidence: 99%